The Importance of Traits of Board of Commissioners, company Size, Profitability and Free Cash Flow in Affecting the Dividend Policy - Ari Wibowo; Erna Setiany (DINASTI RESEARCH, 2023)
This study aims to investigate further relates to dividend policy that utilize in company which affected by characteristics of board of commissioners, business size, profitability as well as free cash flow. Secondary data has been used as source of information that obtained by the publication of financial reports that submitted by the Indonesia Stock Exchange (IDX). This study implemented the purposive sampling strategy to select 180 manufacturing companies which have been registered on the Indonesia Stock Exchange between 2018 and 2020 as research samples. Normality test, heteroscedastic test, autocorrelation test, multicollinearity test, coefficient determination test, linear regression analysis and t-test, those are analysis methods used in this research. The t-test revealed that the characteristics of the commissioners has impact to the company’s dividend policy. While gender representative on the board of commissioners has negatively impacts on dividend policy, number of commissioners and free cash flow both positively affect the dividend policy. The policy relates to dividend distribution did not influence the proportion of independent commissioners, firm size or profitability. However, dividend policy has greatly affected by free cash flow. The research outcomes showed that the proportion of independent commissioners in a company usually lower than the total of commissioners owned by the company. Those Companies tends to allocate retained earnings to develop more profitable projects to get maximum profits. Companies that generate large inflows of free cash are more likely to make large dividend payments to reduce waste on unprofitable projects.